Reshaping identities musically: a cross-sequential research with children - Milhano, Sandrina (2022)
This paper aims to discuss and reflect on the development of children's musical identities. One crucial idea was to try to understand why music is exceptionally suited to serve as a tangible model for making sense of both self and self-identity? Why music can be so important in (re)shaping, formulating, and expressing children's individual identiites? A social-cultural approach in music deucation studies was fundamental as pupils' developing musical identiites have origins in biological predisposition towards musicality, end then are shaped by other people, groups, situations, and social institutions that they encounter as they develop in a particular culture. The arguments presented drawn upon literature from socialogy and the psychology of music, ethnomusicology, neuroscience, music education, and community music to demonstrate the diversity of inquiry about musical identities. (...)